Cellular advective-diffusion drives the emergence of bacterial surface colonization patterns and heterogeneity - Tamara Rossy (Nature Portfolio, 2019)
In the wild, bacteria grow into structures called biofilms. Here the authors demonstrate that their spatial organization and heterogeneity depends on the interplay between fluid flow and single cell motility; this highlights the role of hydrodynamics in biofilm formation.